GAMBARAN TINGKAT KEPUASAN PASIEN TERHADAP PELAYANAN KESEHATAN GIGI DAN MULUT DI POLIGIGI PUSKESMAS (Jurnal Kesehatan Siliwangi, 2020)
Contentment is a state where the desires, hopes and needs of the cosomer can be met. The patient’s satisfaction is one of the main indicator of health car being used asa measure of measuring the success of the health-care arrangement, measuring the satisfaction of the patient can be an essential part of identifying the quality of care that has bin given. Discovered a picture the level of satisfacion public service in the medical center This type of research is a literature analysis study, in which this study will compare the level of patient satisfaction with services in RSU Puri Raharja, Sudiang health center in Bringin Kanaya Makassar, and Bangkala Health Center Bangkala Jeneponto Regency of South Sulawesi by reviewing the data collected by several researchers. After reviewing literature, the assessment of respondent is viewed from several dimensions unifying those who care for health car, being content with the pace of service given, with being content with the avaibility of tools and infrastructure available in health services. The majority of patient express satisfaction in their dental and oral car. Keywords : Services quality, dental work, medical center.